Characterization of U/Pu particles originating from the nuclear weapons accidents at Palomares, Spain, 1966 and Thule, Greenland, 1968 - Lind, O. C.; Salbu, B.; Janssens, K.; Proost, K.; Garcia-Leon, M.; Garcia-Tenorio, R. (Science of The Total Environment, 2007)
Following the USAF B-52 bomber accidents at Palomares, Spain in 1966 and at Thule, Greenland in 1968, radioactive particles containing uranium (U) and plutonium (Pu) were dispersed into the environment. To improve long-term environmental impact assessments for the contaminated ecosystems, particles from the two sites have been isolated and characterized with respect to properties influencing particle weathering rates. Low (239)Pu/(235)U (0.62-0.78) and (240)Pu/(239)Pu (0.055-0.061) atom ratios in individual particles from both sites obtained by Inductively Coupled Plasma Mass Spectrometry (ICP-MS) show that the particles contain highly enriched U and weapon-grade Pu. Furthermore, results from electron microscopy with Energy Dispersive X-ray analysis (EDX) and synchrotron radiation (SR) based micrometer-scale X-ray fluorescence (micro-XRF) 2D mapping demonstrated that U and Pu coexist throughout the 1-50 microm sized particles, while surface heterogeneities were observed in EDX line scans. SR-based micrometer-scale X-ray Absorption Near Edge Structure Spectroscopy (micro-XANES) showed that the particles consisted of an oxide mixture of U (predominately UO(2) with the presence of U(3)O(8)) and Pu ((III)/(IV), (IV)/(V) or (III), (IV) and (V)). Neither metallic U or Pu nor uranyl or Pu(VI) could be observed. Characteristics such as elemental distributions, morphology and oxidation states are remarkably similar for the Palomares and Thule particles, reflecting that they originate from similar source and release scenarios. Thus, these particle characteristics are more dependent on the original material from which the particles are derived (source) and the formation of particles (release scenario) than the environmental conditions to which the particles have been exposed since the late 1960s.